The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0030883
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomes Induce Regulatory Features in Human and Mouse CD1dhi B Cells: Inhibition of Allergic Inflammation by IL-10 and Regulatory T Cells

Abstract: Chronic helminth infections, such as schistosomes, are negatively associated with allergic disorders. Here, using B cell IL-10-deficient mice, Schistosoma mansoni-mediated protection against experimental ovalbumin-induced allergic airway inflammation (AAI) was shown to be specifically dependent on IL-10-producing B cells. To study the organs involved, we transferred B cells from lungs, mesenteric lymph nodes or spleen of OVA-infected mice to recipient OVA-sensitized mice, and showed that both lung and splenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 32 publications
12
157
0
3
Order By: Relevance
“…Van der Vlugt and colleagues pointed out that schistosomes have the capacity to drive the development of IL-10-producing regulatory CD1d hi B cells in both mice and humans. 35 Furthermore, these B cells are instrumental in reducing experimental allergic inflammation in mice. 35 Fairfax's data suggested that during chronic schistosomiasis, IL-10 promotes the development of a population of B cells within the liver that is responsible for minimizing inflammation and preventing the development of disease in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van der Vlugt and colleagues pointed out that schistosomes have the capacity to drive the development of IL-10-producing regulatory CD1d hi B cells in both mice and humans. 35 Furthermore, these B cells are instrumental in reducing experimental allergic inflammation in mice. 35 Fairfax's data suggested that during chronic schistosomiasis, IL-10 promotes the development of a population of B cells within the liver that is responsible for minimizing inflammation and preventing the development of disease in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, these B cells are instrumental in reducing experimental allergic inflammation in mice. 35 Fairfax's data suggested that during chronic schistosomiasis, IL-10 promotes the development of a population of B cells within the liver that is responsible for minimizing inflammation and preventing the development of disease in the lungs. 36 On the other hand, IL-10 appears to block development of resistance to re-infection with S. mansoni.…”
Section: Discussionmentioning
confidence: 99%
“…En ratones, se describió que la capacidad supresora de la respuesta alérgica que tiene Schistosoma mansoni es dependiente de linfocitos B (LB) productores de IL-10 que se encuentran principalmente en la zona marginal del bazo. Estos inducen la conversión de un mayor número de células al fenotipo CD25+Foxp3 que los LB foliculares del mismo órgano (28). Recientemente, en un modelo de artritis, el desarrollo de esta enfermedad se asoció a un menor número de LB productores de IL-10, lo cual se revirtió al ser tratados con ES-62, un producto de excreción/secreción de Acantocheilonema vitae (32).…”
Section: Linfocitos B Reguladoresunclassified
“…Hay dos estudios en humanos que han indagado la relación entre los Breg y la infección por Schistosoma haematobium. En gaboneses, se encontró un mayor porcentaje de Breg en los infectados que en los no infectados (28). En otra publicación (30), este mismo grupo investigó el papel funcional de estas cé-lulas en el humano y encontró que la depleción de la fracción de linfocitos B CD1d hi resultaba en un menor desarrollo de linfocitos T IL-10 + .…”
Section: Tabla 1 Algunas Poblaciones De Breg Identificadas Y Su Relaunclassified
“…Breg producing IL-10 may limit schistosomiasis-related liver disease [8]. In human immunodeficiency virus (HIV)-1 infection, IL-10-producing B cells, which suppress HIV-1-specific T cell responses in vitro, are elevated in early and chronic HIV-1 infection [9].…”
Section: Regulatory B Cell Response In Hbv Infectionmentioning
confidence: 99%